Rotavirus and illness severity in children presenting with acute gastroenteritis at the primary care out-of-hours service. Issue 1 (1st January 2021) - Wolters, Pien; Holtman, G. A; Weghorst, A. A. H; Knoester, M.; Berger, M. Y.
Abstract: Background: Rotavirus is a common cause of acute gastroenteritis in young children in the Netherlands, where rotavirus vaccination has not yet been implemented. Objectives: To evaluate a difference in illness severity course depending on the presence of rotavirus infection and assess the prevalence of viruses and the referral rate in children with acute gastroenteritis. Methods: A prospective cohort of children aged 6 months to 6 years presenting with acute gastroenteritis to a primary care out-of-hours service from October 2016 to March 2018. Faeces were sampled and sent to a laboratory where viral pathogens were identified and quantified by real-time polymerase chain reaction. Severe course of acute gastroenteritis was defined as a Modified Vesikari Score of ≥11. In addition, we assessed referral rates. Chi-square tests were used to evaluate differences between groups. Results: We included 75 children (34 boys) with a median age of 1.5 years (interquartile range, 0.9–2.0 years). The prevalence of rotavirus was 65.3% (95% confidence interval, 53.5–76.0) with a median cycle threshold of 16.0. Severe course of acute gastroenteritis was present in 31 of 71 children (4 were lost to follow-up). Those with rotavirus (20/47) did not have a severe course more often than those without (11/24): odds ratio, 0.88 (95% confidence interval, 0.33–2.36). Referral rates were comparable for rotavirus (15.2%) and non-rotavirus (14.3%). Conclusion: In out-of-hours primary care, rotavirus is common but not associated with increased severity and higher referral rates in children with acute gastroenteritis.